Regulatory and Scientific Advancements in Gene Therapy: State-of-the-Art of Clinical Applications and of the Supporting European Regulatory Framework - Carvalho, Marta; Sepodes, Bruno; Martins, Ana Paula (Frontiers in Medicine, 2017)
Advanced Therapy Medicinal Products (ATMPs) have a massive potential to address existing unmet medical needs. Specifically, gene therapy medicinal products (GTMPs) may potentially provide cure for several genetic diseases. In Europe, the ATMP regulation was fully implemented in 2009 and, at this point, the Committee for Advanced Therapies (CAT) was created as a dedicated group of specialists to evaluate medicinal products requiring specific expertise in this area. To date, there are three authorized GTMPs and the first one was approved in 2012. Broad research has been conducted in this field over the last few decades and different clinical applications are being investigated worldwide, using different strategies which range from direct gene replacement or addition to more complex pathways such as specific gene editing or RNA targeting. Important safety risks, limited efficacy, manufacturing hurdles or ethical conflicts may represent challenges in the success of a candidate GTMP. During the development process, it is fundamental to take such aspects into account and establish overcoming strategies. This article reviews the current European legal framework of ATMPs, provides an overview of the clinical applications for approved and investigational GTMPs, and discusses critical challenges in the development of GTMPs.